2013
DOI: 10.1093/inthealth/iht031
|View full text |Cite
|
Sign up to set email alerts
|

Local understandings and current barriers to optimal birth intervals among recently delivered women in Sylhet District, Bangladesh

Abstract: In order to increase families' ability to achieve optimal birth intervals, we propose the promotion and integration of healthy fertility practices into antenatal and newborn care interventions, focusing on providing biomedically correct and culturally appropriate information on modern contraceptive methods to the entire family, while simultaneously encouraging open spousal and family communication patterns regarding timing and spacing of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A recent study from rural Bangladesh has demonstrated that incorporating post-partum family planning into the maternal and newborn care packages can significantly improve birth spacing and reduce the risk of preterm birth. Formative research in Sylhet, Bangladesh, has shown that even though there is an understanding of the benefits of healthy spacing, women are not able to make their own pregnancy spacing decisions [57]. Interventions that are suitable for the local culture and that take gender inequalities into account are needed.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from rural Bangladesh has demonstrated that incorporating post-partum family planning into the maternal and newborn care packages can significantly improve birth spacing and reduce the risk of preterm birth. Formative research in Sylhet, Bangladesh, has shown that even though there is an understanding of the benefits of healthy spacing, women are not able to make their own pregnancy spacing decisions [57]. Interventions that are suitable for the local culture and that take gender inequalities into account are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Focus groups with husbands and mothers/mothers-in-law were also included with the understanding that decisions about contraceptive use are not necessarily taken by the woman alone. Formative research conducted at the outset of HFS identified husbands and mothers/mothers-in-law as key influencers of FP decisions [10]. Few studies have examined perceptions around return to fecundity and pregnancy risk after delivery in low resource settings [6,11] or have used behavior change frameworks to identify processes influencing postpartum contraceptive uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of information, education, and communication campaigns and interpersonal communication played important roles in higher use of contraceptives and birth spacing (Sebastian et al 2010). And to increase the effectiveness of birth spacing programs, the promotions should be done into antenatal and newborn care interventions by providing biomedically correct and culturally appropriate information on modern contraceptive methods to the entire family (Lehnertz et al 2013). The role of such interventions with community and groups by the community-based family planning worker, from female relatives, peers, and the media, played important roles in family planning and birth spacing (Mita and Simmons 1995;Bawah et al 1999).…”
Section: Researches and Studies In Birth Spacing And Related Areasmentioning
confidence: 99%